Perbandingan Efektivitas Putih Telur dan Rebusan Daun Sirih terhadap Penyembuhan Luka Perineum Derajat II pada Ibu Nifas - Parmi Rahmayanti; Uci Ciptiasrini; Hidayani Hidayani; Dini Rinjani; Rika Puji Rustiwa; Ai Nurhayati Amalia; Wina Maryana (Jurnal Sehat Mandiri, 2026)
Perineal wounds in postpartum women often cause discomfort and risk of infection if not properly managed. This study aimed to determine the effect of boiled egg whites and betel leaf decoction on the healing of second-degree perineal wounds among postpartum mothers at the Sindangbarang Inpatient Health Center, Cianjur Regency, in 2025. The research employed a quasi-experimental design with a post-test group design involving 20 respondents divided into two intervention groups. Data were collected using the REEDA observation sheet and analyzed with the Mann-Whitney test. The results showed a significant difference between the egg white and betel leaf groups with a p-value of 0.023 (<0.05), indicating that both interventions had a positive effect on perineal wound healing. However, egg whites were more effective in accelerating tissue regeneration, while betel leaf decoction acted as a natural antiseptic. It can be concluded that boiled egg whites have a stronger effect in promoting the healing of second-degree perineal wounds. It is recommended that postpartum mothers, midwives, and healthcare facilities utilize natural ingredients such as egg whites and betel leaves as safe, affordable, and accessible non-pharmacological alternatives for perineal wound care.